Sub-Lethal Effects of Predators in Aquaculture: Assessment of Chronic Exposure to Conspecific Alarm Substance on Feeding and Growth Performances of Nile Tilapia - Rafaela Torres Pereira; Alexandre Luiz Arvigo; Caio Akira Miyai; Augusto Rysevas Silveira; Percília Cardoso Giaquinto; Helton Carlos Delicio; Leonardo José Gil Barcellos; Rodrigo Egydio Barreto (Fishes)
In aquaculture practices, fish are mostly protected from lethal actions of predators. However, sub-lethal effects can be challenging to prevent, as they may be associated with chemical cues signaling predation risk that easily dissolve and spread in water, serving as potential stressors. These cues originate from predators, stressed or injured prey releasing blood, a conspecific alarm substance (CAS), and/or other bodily fluids. In this study, we simulated a small-scale net cage system and assessed the feeding and growth of Nile tilapia exposed chronically to a CAS. Nile tilapia, an invasive species in many aquatic systems, frequently coexist freely alongside those cultivated in cages. Consequently, caged tilapia may regularly be exposed to a CAS, potentially leading to chronic stress and impacting growth and development. Fish were exposed daily to either a CAS or a control vehicle (distilled water) for 45 days (one fish per cage). Fish in both conditions exhibited similar increases in body mass, weight gain, and length over time and displayed an allometric negative growth profile, indicating that the CAS did not affect the length–weight relationship as well. Specific and relative growth rates, condition factor, body axes, food intake, and feeding conversion efficiency were also unaffected by the CAS over time. This body of evidence suggests that the CAS did not act as a chronic stressor for caged Nile tilapia and a possible explanation is habituation.